An Empirical Test of Urban Labor Matching - Miles Finney (European Regional Science Association (ERSA), 2006)
This study tests for the labor matching efficiency of cities by examining the relationship between urbanization and the skills variation of public school principals. The results imply urban labor markets are generally more efficient at matching the skills of residents to the skills required by employers. The variation in labor skills among school principals is found to decrease with urban size, which is evidence that urbanization fosters more efficient labor matches.
Keywords: 330